Keabsahan Praktik Dark Patterns Terhadap Pemerolehan Persetujuan Pemrosesan Data Pribadi di Indonesia (RechtJiva, 2025)
Advances in digital technology have changed the way personal data is collected and processed, often involving dark patterns, which are manipulative interface designs that influence users' consent unconsciously. This research aims to analyze the validity of consent to personal data processing that contains elements of dark patterns based on treaty law and personal data protection principles. In addition, a comparison is made with regulations in the European Union and California to recommend a more effective regulation in Indonesia. This research uses normative juridical method with statutory, case, and comparative approaches. Primary data comes from Law Number 27 Year 2022 on Personal Data Protection (UU PDP), while secondary data comes from related legal literature. The results show that the PDP Law has not explicitly regulated the prohibition of dark patterns, thus opening up opportunities for manipulation in consent. The standard of valid consent in Article 20 paragraph (2) letter a of the UU PDP is still unclear compared to the GDPR in the European Union and the CCPA in California. This study recommends revising the UU PDP to include a prohibition of dark patterns and affirmation of the elements of valid consent, in order to improve personal data protection in the digital era.